Tornadoes - Ohare, Ted; Nang Chan Yeema (Los Angeles, California, United States Fitzgerald Books, 2007)
Illustrations and text introduce tornadoes, from what causes them, to how they are measured, tracked, and predicted.
Keywords: Juvenile Nonfiction